Dental Pulp Regeneration: Insights from Biological Processes - Retana-Lobo DDS, MSD, Cristina (Odovtos - International Journal of Dental Sciences, 2017)
One of the major approaches on dentistry research in this century is the development of biological strategies (tissue engineering) to regenerate/ biomineralize lost dental tissues. During dentin-pulp regeneration, the interaction between stem cells, signaling molecules, biomaterials and the microenvironment in the periapical area drives the process for dental pulp tissue engineering. Understanding the signaling mechanisms and interactions involved with the biological process for the formation of a new tissue, is essential. The knowledge of the micro-environment is the key for the application of tissue engineering. The present article is a short review of the current state of this topic, with the purpose of showing insights of pulp regeneration.